Penerapan Kedisiplinan dan Budaya Kerja Islam serta Pengaruhnya terhadap Kinerja Karyawan: Studi Kasus CV Garmen Bogor - Fuad, Ryan Mafatihul; Ismuni, Mutdi; Haryadi, Rofiq Noorman (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study addresses the urgent need for organizations to cultivate a work environment rooted in discipline and Islamic values, particularly within companies guided by Sharia principles. In an increasingly competitive and value-driven business world, aligning workplace behavior with religious ethics can foster a harmonious and productive atmosphere. This research employs a descriptive quantitative approach, involving all employees at CV Garmen Bogor, with data collected through questionnaires, observations, and literature studies. Findings reveal that both discipline and Islamic work culture have a meaningful and positive impact on employee performance. Discipline encourages consistency, accountability, and time management, while an Islamic work culture fosters integrity, mutual respect, and a strong sense of responsibility. Together, these factors create a balanced and ethical workplace that not only improves individual performance but also enhances team collaboration and organizational commitment. The implications suggest that integrating Islamic values into daily operations is not only compatible with modern productivity standards but also reinforces a culture of excellence. Companies that prioritize ethical behavior and structured discipline are more likely to achieve long-term success and employee satisfaction.